SMART-NFE Teaching on Improving Learner’s Motivation & Productivity: SMART Teaching With NFE Principles - Lenni Mantili Hutauruk (UNIB Press, 2022)
SMART-NFE Teaching is a specific, measurable, Active, Relevant, and time-bound teaching strategy with the NFE principle taken into consideration, improving student engagement and increase learning productivity significantly. The newest curriculum of Indonesian encourages the lesson plan to be designed with a SMART learning objective, as the SMART learning objective is already well-known to be used in setting successful business strategies. In this paper, the SMART objective with modification to the learning environment will be adapted with the addition of the Nonformal Education Principle which will increase the probability of the successfulness of learning for college students. This paper is conducted by the experiment method, the SMART-NFE Teaching is applied directly to college students with respondents from three classes. Two classes as the treatment recipients and one class are the control class. The data was collected through qualitative to examine the learning motivation and quantitative methods to see the learning productivity as shown in students’ midterm scores along with student projects. Furthermore, this paper argues that SMART-NFE Teaching increases the participant’s learning motivation and learning productivity. This is to be achieved by using a teaching strategy with a specific, measurable learning objective, a set objective that encourages the learners to be active, a learning objective that is close to the student’s real life, and an agreeable time-bound. And, to make sure the learner is willing to participate, the learning strategy also applies the nonformal education principle which will make sure the learner voluntary engages in the learning activity, hence able to follow the learning activity with the feeling of enjoyment dan excitement for the next lesson as the student mention in the questionnaire. This paper encourages the use of the Nonformal Education Principle should be considered in formal education. Keywords: SMART Teaching, NFE Principle, Learning Motivation, Learning Productivity, Learning Strategy